Development and Validation of a Scale to Assess the Factors Contributing towards School - Faseeha Khursheed, Attiya Inam, Muhammad Abiodullah, (PJE, 2023)
School refusal behavior is a serious issue in Pakistan which has remained unnoticed. To understand the intensity of the issue, it is important to understand the school-related factors for school refusal. There was no tool available to study these factors in cultural context of Pakistan. This study aimed to develop a scale to measure different dimensions of school factors causing school refusal behavior among middle school students.Both qualitative and quantitative data were collected for this purpose.